Using human translators’ skills to bridge the digital communication divide between migrants and public services through an accessibility assessment: Outsmarting machines - Ruiz Cortés, Elena (Peter Lang, 2023)
The changing language industry requires experts who are able to provide new services. In the face of the advance of machine translation and artificial intelligence, it is vital to foreground the added value of human translators’ skills to provide services that machines cannot provide in this industry (Massey et al., 2022). On this understanding, in this chapter we highlight the added value of human translators’ skills to provide services that machines cannot provide in the current language industry beyond the scope of automation. Specifically, we contend that translators can provide an accessibility assessment of defective digital resources created by the Public Administration, which will contribute to enhance the digital communicative divide occurring in institutional contexts. Thus, after introducing our accessibility assessment, we will implement the first phase of this accessibility assessment and, using a case study, we will showcase its usefulness as a first step to enhance digital communication between Spanish authorities and migrants.
https://www.peterlang.com/repository-policy/
Keywords: Traducción en los servicios públicos; Human translators; Translators’ skills; Digital communication divide; Accessibility assessment; Public administration